Analysis of Women's Activities in Uzbekistan (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article summarizes the decisions and laws adopted in the Republic of Uzbekistan during the years of independence to support women and their activities in every way. The analysis of scientific researches that shed light on the participation of women in socio-economic and political processes in Uzbekistan is presented. Also, information is provided about articles by foreign scientists who have commented on the issues of gender equality.